2000
DOI: 10.1021/jp002264d
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Scandium and Titanium Carbide Cations, ScC+and TiC+. Ground and Low-Lying States

Abstract: The monopositive scandium and titanium carbides, ScC + and TiC + , have been studied by multireference methods coupled with quantitative basis sets. We have constructed potential energy curves for the ground and twelve low-lying excited states for both species, focusing on dissociation energies and bonding mechanisms. We have found that the ground states of ScC + and TiC + are of 3 Π and 2 Σ + symmetries, with binding energies (D 0 ) of 68.8 (71.5) and 85.2 (86.7) kcal/mol at the MRCI (MRCI+Davidson correction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 21 publications
4
34
1
1
Order By: Relevance
“…The binding mode consists of 2p and 1/2 bonds and is identical to the one found in the ground X 2 AE þ state of TiC þ [9][10]. The 'extra' electron is placed in an orbital of d symmetry, just observing the chemical bond and defining the spatial symmetry.…”
Section: Electronic Structure Of Vanadium and Chromium Carbide Cationsmentioning
confidence: 74%
See 3 more Smart Citations
“…The binding mode consists of 2p and 1/2 bonds and is identical to the one found in the ground X 2 AE þ state of TiC þ [9][10]. The 'extra' electron is placed in an orbital of d symmetry, just observing the chemical bond and defining the spatial symmetry.…”
Section: Electronic Structure Of Vanadium and Chromium Carbide Cationsmentioning
confidence: 74%
“…with the 1986 limited MRCI/DZ value of 31.5 kcal mol À1 ) [12]. As our experience with ScC þ , TiC þ , and VC þ indicates [9,10] this value should fall short to an experimental value by about 2-3 kcal mol À1 due to the basis set incompleteness. The final D 0 ( 4 AE À ) value would then equal to about 56 kcal mol À1 , still lower from the experiment by maybe about 10 kcal mol À1 .…”
Section: Crmentioning
confidence: 81%
See 2 more Smart Citations
“…In addition, Wang et al [10] have found the first and only spectroscopic and electronic information on TiC x À (x = 2-5) provided by photoelectron spectra. The monopositive titanium carbides, TiC + , have also been studied by multireference methods coupled with quantitative basis sets [11].…”
Section: Introductionmentioning
confidence: 99%